2008
DOI: 10.1093/jpepsy/jsn049
|View full text |Cite
|
Sign up to set email alerts
|

Review: Genetics of Attention Deficit/Hyperactivity Disorder

Abstract: Ideally, one day specific genes with major effects and specific risk factors with which they interact will be identified and we will be able to implement personalized medicine. Knowledge of such genes will allow us to identify specific diagnostic biological markers. In addition, defining the target genes is the first step in developing novel drug therapies to treat the ADHD symptoms that lead to impairment. Furthermore, such markers could also identify at risk individuals at a younger age in order to implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 88 publications
1
74
0
3
Order By: Relevance
“…There is considerable evidence that genetic factors are important in the etiology of ADHD [13,14]. Like most complex disorders, ADHD is presumed to have a polygenic etiology.…”
Section: Genetics and Adhdmentioning
confidence: 99%
“…There is considerable evidence that genetic factors are important in the etiology of ADHD [13,14]. Like most complex disorders, ADHD is presumed to have a polygenic etiology.…”
Section: Genetics and Adhdmentioning
confidence: 99%
“…The short variant results in reduced transcription of the transporter protein leading to slower reuptake of 5-HT leaving more of it available to excite or inhibit downstream neurons. The long variant, especially the homozygous (L/L) genotype, is associated with ADHD because this variant rapidly clears 5-HT from the synapse resulting in its reduced availability of the behavior-inhibiting -brake‖ (Wallis et al, 2008). The BAS/BIS motivating/inhibiting system has been considered conceptually to be modern neuroscience's analog of the Freudian Id and Superego, with BAS-BIS balance being the Ego (Walsh, 2009).…”
Section: -Htt Genementioning
confidence: 99%
“…The comorbidity of ADHD with many other disorders strongly suggests that epistasis (the interaction of genes) and pleiotropy (the influence of a single gene on more than one phenotypic trait) are involved as well as genetic heterogeneity (Wallis et al, 2008). The odds of inheriting alleles for comorbid disorders is determined by genetic linkage studies and is quantified by LOD (log of the odds ratio) scores.…”
Section: Adhd CD and Odd Comorbiditymentioning
confidence: 99%
“…ADHD disproportionately affects children living in poverty and those who receive Medicaid. [2] While twin studies have demonstrated a strong genetic basis for ADHD, with estimates of 70%-80% heritability, [4] a number of individual-and family-level factors have also been found to be associated with ADHD incidence, including race/ethnicity, gender, [5] birth weight, [6] prenatal, [7,8] and secondhand smoke exposure, [9] lead poisoning, [10] poverty, [11] single parent households, [12] parenting practices, [13] maternal education level, [5] maternal mental health, [13] early traumatic experiences, [10,15] increased TV/computer exposure, [10,15] and household mobility. [16] The development of ADHD and its level of severity in a child likely represent an interaction between genetic susceptibility and environmental influences of place, family, and circumstance.…”
Section: Introductionmentioning
confidence: 99%